Structural basis of Staphylococcus epidermidis biofilm formation: mechanisms and molecular interactions - Büttner, Henning; Mack, Dietrich; Rohde, Holger (Frontiers in Cellular and Infection Microbiology, 2015)
Staphylococcus epidermidis is a usually harmless commensal bacterium highly abundant on the human skin. Under defined predisposing conditions, most importantly implantation of a medical device, S. epidermidis, however, can switch from a colonizing to an invasive life style. The emergence of S. epidermidis as an opportunistic pathogen is closely linked to the biofilm forming capability of the species. During the past decades, tremendous advance regarding our understanding of molecular mechanisms contributing to surface colonization has been made, and detailed information is available for several factors active during the primary attachment, accumulative or dispersal phase of biofilm formation. A picture evolved in which distinct factors, though appearing to be redundantly organized, take over specific and exclusive functions during biofilm development. In this review, these mechanisms are described in molecular detail, with a highlight on recent insights into multi-functional S. epidermidis cell surface proteins contributing to surface adherence and intercellular adhesion. The integration of distinct biofilm-promoting factors into regulatory networks is summarized, with an emphasis on mechanism that could allow S. epidermidis to flexibly adapt to changing environmental conditions present during colonizing or invasive life-styles.